An integrated indicator on regional ecological civilization construction in China. Issue 1 (2nd January 2016) - Liu, Moucheng; Liu, Xingchen; Yang, Zhenshan
Abstract : China has come up with ecological civilization as one of major goals to improve its ecological sustainability during development in future. Under this broad framework, social, economic and natural ecosystems are expected to develop in harmony. However, there is lack of evaluation mechanism for this newly proposed strategy. Therefore, in this article, ecosystem services, Ecological Footprint and gross domestic product per capita were selected in order to reflect the resource endowment, human occupation on natural capital, and the economic growth. Thus, an integrated indicator was constructed from the three indexes based on the linear correlation among them, and we provided comprehensive evaluation on ecological civilization construction in the provinces and municipalities in China in 2010. When it comes to the indicator of ecological civilization construction, Hainan province has the greatest value which is 0.5091 and Beijing municipality has the smallest value which is 0.0377. At last, the article analyzed the ecological pressure and efficiency in ecological civilization construction in China. The results contribute to scientific and objective evaluation of regional ecological civilization construction in order to properly make decisions and take actions.